Peculiarities of decision making by authorities in Ukraine in the transformation period - Natalya Podvirna (Facta Simonidis, 2013)
This article analyzes the process of as well as the impact of transformation processes, political crisis and personal characteristics of governmental actors in policy-making. The present research concludes that the speed and efficiency of decision-making depends on the political and legal standards of government entities, their competence, as well as the ability to use the available resources and take responsibility for decision-making. During the transformations and political crisis there are a number of factors that affect the decision-making process, such as compliance with time parameters in deciding the objective and full-scale clear awareness of decision-making by the authorities.